Ecofeminism in Kajang fashion: Gender Semiotics and Sustainability - Ahmad Subair (Sean Institute, 2025)
This ethnographic research examines the traditional black clothing of the Ammatoa Kajang community as a model for ecofeminist-based climate adaptation. Through participant observation, in-depth interviews, and focus group discussions (FGDs) titled Andingingi, it was found that this gender-neutral clothing reflects the Pasang Ri Kajang philosophy of equality, produced in a zero-waste manner using organic cotton, natural dyes, and hand-woven fabrics that emit <0.5 kg of CO₂ per piece. Women, as the primary artisans, utilize weaving as a household economic resource that supports food and climate security, linked to sacred forest conservation. Recommendations include recognizing customary forest laws and integrating local knowledge into national policies